Pawing by Standardbred Racehorses: Frequency and Patterns - BUTLER, Christina L. (The Japanese Society of Equine Science, 2014)
The objectives of this study were to determine the prevalence of pawing behavior in a population of Standardbred racehorses and the relationship of pawing frequency to time of day. Standardbreds (n=41) were observed using instantaneous scan sampling twice daily, in the morning before training and in the afternoon after training. A majority of the horses, twenty-four (58.5%) of the 41 horses showed pawing behavior at least once (median=7, interquartile range=2–15). After training, there were a median of 4 (interquartile range 1–11) observations of pawing or 11.2% of total observations. In the morning, before training, there were 3 (0–3.25) pawing observations, or 9.1% of total observations. There was a significantly greater frequency of pawing in the afternoon (P=0.0005). They pawed less on Sunday afternoons when they had not trained. Pawing may be related to exercise and, possibly, discomfort.